2020
DOI: 10.1371/journal.pone.0232342
|View full text |Cite
|
Sign up to set email alerts
|

Parrot bornavirus in naturally infected Brazilian captive parrots: Challenges in viral spread control

Abstract: Psittaciform orthobornaviruses are currently considered to be a major threat to the psittacine bird population worldwide. Parrot bornavirus (PaBV) was identified recently in Brazil and, since then, few studies have been conducted to understand the epidemiology of PaBV in captive psittacine birds. In the present study, natural infections by PaBV in South American parrots were investigated in two breeding facilities: commercial (A) and conservationist (B). Thirty-eight psittacine of 21 different species were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This study incorporated a comprehensive set of PaBV sequences and available epidemiological information to present a global view of this virus’s diversity. In Brazil, a few molecular studies with phylogenetic analyses on avian bornaviruses have mainly indicated the presence of the PaBV-4 genotype in captive and free-living birds [ 11 , 12 , 14 ]. PaBV-8 was identified and proposed as a new genotype but has only been detected in Brazil [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study incorporated a comprehensive set of PaBV sequences and available epidemiological information to present a global view of this virus’s diversity. In Brazil, a few molecular studies with phylogenetic analyses on avian bornaviruses have mainly indicated the presence of the PaBV-4 genotype in captive and free-living birds [ 11 , 12 , 14 ]. PaBV-8 was identified and proposed as a new genotype but has only been detected in Brazil [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, known for its highly diverse avifauna and being the richest in psittacines, PaBVs have been detected in captive and free-ranging psittacines and Passeriformes [ 11 , 12 , 13 ]. These infections have mainly corresponded to the PaBV-4 genotype [ 11 , 12 , 14 ], with the PaBV-8 genotype unique to this country [ 15 ]. This study describes a severe case of PDD in a sulphur-crested cockatoo (Cacatua galerita) and includes comparative molecular and evolutionary analysis with other PaBV strains worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Parrot bornavirus is the causative agent of proventricular dilatation disease (PDD), and infection leads to a chronic neurological and digestive disorder in psittacine birds. PaBV presence has been reported in Brazil [4][5][6]; Germany [7][8][9][10][11]; France and Spain [9]; Portugal [12]; the Netherlands [8]; Sweden [13]; Austria, Switzerland, Hungary, and Australia [14]; the United States [15][16][17][18]; Canada [19,20]; South Africa [21]; the Czech Republic and Slovakia [22]; Qatar [23]; Israel [18]; Malaysia [24]; Thailand [25]; China [26]; South Korea [27]; and Japan [28,29]. The detection rates of PaBV vary significantly among these countries.…”
Section: Introductionmentioning
confidence: 99%